Pragmatic analysis of complaints by Iranian speakers of English - Masjedi, Narges (2017)
Complaint speech act is a face threatening act and it happens when a speaker reacts with anger to things which go wrong or to a speech or an action which affected on him or her unfavorably. Therefore, complaints by its nature can engender social relationship breakdown. Despite this, a complainer can use politeness when he or she aims to maintain a good relationship with complainee or to mitigate the severity of his or her complaint and face threat. This study aims to investigate the complaint speech act and politeness strategies of Iranian learners in communication with other nationalities in the academic context of a university. The objectives of the study are to investigate what complaint strategies are used by Iranian learners, how their complaints are structured, and how politeness is displayed in their complaint when communicating in English with other nationalities. The sample was made up of 50 Iranian postgraduate learners, 25 male and 25 female, and the data was collected by means of background questionnaire and open-ended Discourse Completion Test in the type of critical incidents. The study is qualitative and employs pragmatics as the approach to data analysis. The data were analyzed through complaint taxonomies; Trosborg’s (1995) taxonomy was used to analyze complaint strategies while Rinnert and Nogami’s (2006) taxonomy was used to analyze complaint structures. Politeness strategies were analyzed through Brown and Levinson’s (1987) taxonomy.The findings show that Iranians used a variety of strategies and structures when complaining in different situations and contexts; their most preferred complaint strategy however was Indirect Accusation and their utterances were mostly structured as Complaint followed by Request (C+R). Negative Politeness especially Be Conventionally Indirect was the most frequently used politeness strategy by the respondents. In sum, the study shows that Iranians are indirect and show negative politeness as they try to minimize the face threatening act of complaining. Iranians’effort to be indirect can be considered as part of Iranian culture to avoid impairing their relationship with hearers.